2006
DOI: 10.1105/tpc.105.039388
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis Is Essential for Pathogenic Development in the Corn Smut Fungus Ustilago maydis

Abstract: It is well established that polarized exocytosis is essential for fungal virulence. By contrast, the contribution of endocytosis is unknown. We made use of a temperature-sensitive mutant in the endosomal target soluble N-ethylmaleimide-sensitive factor attachment protein receptor Yup1 and demonstrate that endocytosis in Ustilago maydis is essential for the initial steps of pathogenic development, including pheromone perception and cell-cell fusion. Furthermore, spore formation and germination were drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 49 publications
1
150
0
Order By: Relevance
“…In agreement with some role of Pcl12 in the formation of the conjugation tubes, we found that pcl12 was induced after pheromone treatment ( Figure 7C). These data suggest that Pcl12 plays a role in the polar growth of the conjugation tube, although we cannot exclude some indirect effect such as the possibility that Pcl12 participate in pheromone sensing as it has been recently proposed for Myo5 and Yup1 (Weber et al, 2003;Fuchs et al, 2006). To address this issue, we took advantage of the fuz7DD allele, which encodes an activated version of the mitogenactivated protein kinase (MAPK) kinase involved in pheromone response (Banuett and Herskowitz, 1994;Mü ller et al, 2003), since cells expressing this allele under the arabinose-induced crg1 (D) Pcl12-induced filamentation is dependent on cdk5.…”
Section: Absence Of Pcl12 Delays the Formation Of The Conjugation Tubementioning
confidence: 90%
“…In agreement with some role of Pcl12 in the formation of the conjugation tubes, we found that pcl12 was induced after pheromone treatment ( Figure 7C). These data suggest that Pcl12 plays a role in the polar growth of the conjugation tube, although we cannot exclude some indirect effect such as the possibility that Pcl12 participate in pheromone sensing as it has been recently proposed for Myo5 and Yup1 (Weber et al, 2003;Fuchs et al, 2006). To address this issue, we took advantage of the fuz7DD allele, which encodes an activated version of the mitogenactivated protein kinase (MAPK) kinase involved in pheromone response (Banuett and Herskowitz, 1994;Mü ller et al, 2003), since cells expressing this allele under the arabinose-induced crg1 (D) Pcl12-induced filamentation is dependent on cdk5.…”
Section: Absence Of Pcl12 Delays the Formation Of The Conjugation Tubementioning
confidence: 90%
“…In this fungus, the only membranous cargo known to travel in a bidirectional fashion along MTs is EEs (23). Similar to that in humans (24) and amoebas (10), kinesin-3 motors carry the EEs to MT plus ends at the hyphal tip (anterograde motility) (25,26), where they support polarized growth and mating by local endocytic recycling (23,27). The importance of the retrograde dynein-driven EE motility is unknown, but it might mediate communication with the nucleus (28).…”
mentioning
confidence: 98%
“…If the apical dynein accumulation serves as a loading zone, all EEs have to reach the hyphal tip before changing direction. We tested this by visualizing anterograde motility of photoactivatable green fluorescent protein (paGFP) fused to the small endosomal GTPase Rab5a, which has been shown to localize to EEs in U. maydis (27). The use of this GFP variant enabled us to visualize subsets of EEs and reduced interferences.…”
Section: Early Endosomes Switch Between Long Phases Of Anterograde Andmentioning
confidence: 99%
“…Promising candidate mRNAs for Khd4 that contain AUACCC, but were not detected as differentially expressed in our microarray analysis, are cdc42, yup1, and spa2, encoding a small G protein, a putative t-SNARE, and a polarisome component, respectively (Wedlich-Söldner et al 2000;Mahlert et al 2006;Carbo and Perez-Martin 2008). Deletion of cdc42 leads to defects in cytokinesis and virulence (Mahlert et al 2006), loss-of-function mutants in yup1 are affected in cell morphology and virulence (Wedlich-Söldner et al 2000;Fuchs et al 2006), and spa2D strains exhibit increased cell diameters and form shorter filaments, albeit deletion strains are fully pathogenic (Carbo and Perez-Martin 2008). Another candidate for Khd4 regulation is AUACCC-containing mRNA clp1 encoding a key factor of clamp formation, which is essential for pathogenicity.…”
Section: What Is the Cellular Role Of Khd4?mentioning
confidence: 99%
“…strain SG200R (SG200 variant expressing cytoplasmic mRfp, monomeric version of the red fluorescent protein) (Bölker et al 1995;Campbell et al 2002;Fuchs et al 2006). This strain enables plant infection experiments without prior mating.…”
Section: Mutations In Kh Domain 3 Drastically Affect Pathogenic Develmentioning
confidence: 99%